A new X linked recessive deafness syndrome with blindness, dystonia, fractures, and mental deficiency is linked to Xq22. Issue 4 (April 1995) - Tranebjaerg, L; Schwartz, C; Eriksen, H; Andreasson, S; Ponjavic, V; Dahl, A; Stevenson, R E; May, M; Arena, F; Barker, D
Abstract : X linked recessive deafness accounts for only 1.7% of all childhood deafness. Only a few of the at least 28 different X linked syndromes associated with hearing impairment have been characterised at the molecular level. In 1960, a large Norwegian family was reported with early onset progressive sensorineural deafness, which was indexed in McKusick as DFN-1, McKusick 304700. No associated symptoms were described at that time. This family has been restudied clinically. Extensive neurological, neurophysiological, neuroradiological, and biochemical, as well as molecular techniques, have been applied to characterise the X linked recessive syndrome. The family history and extensive characterisation of 16 affected males in five generations confirmed the X linked recessive inheritance and the postlingual progressive nature of the sensorineural deafness. Some obligate carrier females showed signs of minor neuropathy and mild hearing impairment. Restudy of the original DFN-1 family showed that the deafness is part of a progressive X linked recessive syndrome, which includes visual disability leading to cortical blindness, dystonia, fractures, and mental deficiency. Linkage analysis indicated that the gene was linked to locus DXS101 in Xq22 with a lod score of 5.37 (zero recombination). Based on lod-1 support interval of the multipoint analysis, the gene is located in a region spanning from 5 cM proximal to 3 cM distal to this locus. As the proteolipid protein gene (PLP) is within this region and mutations have been shown to be associated with non-classical PMD (Pelizaeus-Merzbacher disease), such as complex X linked hereditary spastic paraplegia, PLP may represent a candidate gene for this disorder. This family represents a new syndrome (Mohr-Tranebjaerg syndrome, MTS) and provides significant new information about a new X linked recessive sydromic type of deafness which was previously thought to be isolated deafness.